Dynamic physiotherapy for all patients admitted to the ICU according to their clinical status-describing a quality improvement program - Carvalho Brugger Sulamita; Caballero Jesus; Curia Davinia; García Eva; Sabate Ivan; Sancho Marisa; Ariza Gemma (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Immobilization and prolonged bed rest is associated with many complications, including delirium, muscle atrophy, decubitus ulcers, atelectasis, and bone demineralization. Early mobilization strategies in the ICU are safe and may result in the prevention and reduction of critical illness polyneuropathy, delirium, ICU and hospital length of stay, may decrease mortality during hospitalization, and improve the patient's quality of life after hospital discharge.